The Nicotianamine Synthase Gene Is a Useful Candidate for Improving the Nutritional Qualities and Fe-Deficiency Tolerance of Various Crops - Nozoye, Tomoko (Frontiers in Plant Science, 2018)
With the global population predicted to grow by at least 25% by the year 2050, the sustainable production of nutritious foods will be necessary for human health and the environment. Iron (Fe) is an essential nutrient for both plants and humans. Fe is poorly soluble, especially at high pH levels, at which it is difficult for living organisms to accumulate sufficient Fe. In plants, Fe deficiency leads to low yield and poor nutritional quality, as it significantly affects chlorophyll synthesis. Fe deficiency is a worldwide agricultural problem that is especially serious in soils with a high pH, such as calcareous soils, which comprise approximately 30% of cultivated soils worldwide. Genetic improvements in crops that can tolerate Fe deficiency will be required to meet the demands for crop production and could ultimately contribute to the amelioration of global warming. Nicotianamine (NA) is an Fe chelator in plants that is involved in metal translocation in the plant body. In mammals, NA inhibits angiotensin I-converting enzyme, which plays a key role in blood pressure control. It was recently shown that the enhancement of NA production using nicotianamine synthase is useful for increasing not only NA but also Fe and Zn levels in crops such as rice, soybean, and sweet potato. Additionally, these plants showed Fe-deficiency tolerance in calcareous soil. These results suggested that NAS overexpression simultaneously improves food quality and increases plant production. This review summarizes progress in generating crops overexpressing NAS.